Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Terhadap Pemahaman Konsep Matematis Siswa Kelas VII SMPN 5 Padang - Juita, Yora; Rahmi, Rahmi; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
This research based on the lack of comprehension of the mathematical concepts that students look at learning outcomes math class VII student SMPN5 Padang and less active in group discussions. This study aimed to determine whether students comprehension of mathematical concepts with the application of cooperative learning type think pair share a better comprehension of the mathematical concepts that students applying conventional teaching class VII SMPN 5 Padang academic year 2012/2013, and to determine whether the application of Cooperative Learning type Think Pair Share cooperative Mathematics Learning effective. This type of research is experimental research on the subject with a random design. The research instrument is shaped final essay test with a reliability test is r11 = 0.84, and a questionnaire study of learning effectiveness. Based on questionnaire data obtained percentage of the overall indicator of the effectiveness of learning by 85,26% including the highly effective criteria. Hypothesis testing using t-test of the parties with the help of MINITAB, obtained p-value = 0.011 is less than α of 0.05, then reject H0. So, it can be concluded that the students comprehension of mathematical concepts with the application of cooperative learning type Think Pair Share (TPS) is better than the students understanding of mathematical concepts by applying conventional learning class and implementation of cooperative learning model Think Pair Share (TPS) is very effective in learning mathematics.